(untitled) (Eurasian Research Bulletin, 2024)
This article presents the sociological analysis of the social stratification in Turkestan occurred in the end of the 19th and the beginning of the 20th centuries. Famous national researchers were able to reveal and present the main layers or strata of population including vulnerable groups.